Soluciones tecnológicas de las farmacias comunitarias al desabastecimiento de medicamentos: aplicación del modelo colaborativo en red y 'big data'. - Martín Lázaro, Rubén; Castro, Luis; Molinero, Ana; Acosta, Jaime (Farmacéuticos Comunitarios, 2020)
Background: Medicine shortages cause negative economic, clinical and humanistic results for patients, also generating additional workload for healthcare stakeholders. Luda Farma (LF) is a pharmacy electronic management and collaborative platform aimed at improving efficiency in stock control, and to help pharmacists by providing them a collaborative tool that allows sharing specific information on the stock of particular medications among pharmacies. Objectives: To analyze the number of medicines in short supply (according to the AEMPS and CISMED listings) that patients locate through the LF platform. To identify which medicines in short supply are located through the platform. Method: This retrospective, observational study, used the data generated through LF during the year 2019 (from January 1st to December 31st). LF was used to search for those medicines in short supply according to CISMED and AEMPS. Data from the network was searched at the CISMED and the AEMPS listings. Data were processed with programming language R. Results: 389 pharmacies that freely and voluntarily affiliated to the LF network participated. They carried out 7,628 orders between pharmacies: 1993 of those medicines had supply problems according to the AEMPS, and 1,794 medicines had supply problems according to the CISMED listings. The drugs with the most significant number of reservations were: Apocard® 100mg 60 tablets, Trankimazin Retard® 0.5mg 30 tablets, and Elontril® 150 mg 30 tablets. Conclusions: LF helps pharmacists by providing an on-site solution to patients who cannot find the drugs they are looking for, lessening the impact of drug shortages.